ANALISIS RESEPSI E-WALLET DALAM VIDEO IKLAN DANA DOMPET DIGITAL INDONESIA PADA MAHASISWA PEKANBARU - Reza Rinaldi; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Digital wallets are currently a trend in various countries including Indonesia, which has led to digital transactions in various groups, including one of the Pekanbaru students. Students as media audiences accept many habits of transacting digitally from advertisements in the media. For example, through a video advertisement for the Dana Dompet Digital Indonesia which is currently in demand in Indonesia regarding digital wallet transactions. Students who watch the advertisement video have a new habit of transacting in various ways that can affect the extent to which digital wallets can be adopted in everyday life for transactions. This study aims to determine the dominant position of reading, negotiated reading and oppositional reading of Pekanbaru students towards the new transaction habits of E-wallet users in the video advertisement of the Dana Dompet Digital Indonesia on Youtube          This research uses descriptive qualitative research that focuses on e-wallet user receptions. The research data was obtained through interviews, observation and documentation with five informants who were selected using purposive techniques, namely Adinda, Naila, Fajri, Fariz and Yuris. The data analysis technique used is the reception analysis method which consists of data collection, analysis and interpretation of reception data. Meanwhile, the data validity checking technique used source triangulation.            The results of the first study were that four informants had dominant perceptions of e-wallet applications and one informant had negative perceptions of the application. Second, the five informants perceive the location of the transaction and the scene in the advertisement as negotiated. Third, none of the informants received an oppositional view of the video advertisement for Dana Dompet Digital Indonesia. The difference in how informants perceive e-wallets is due to several factors, namely age, education, experience and culture, which can also distinguish the way informants perceive e-wallets. Key words: Reception Analysis, E-wallet.